Experimental Investigation on the Elicitation of Subjective Distributions - Barrera-Causil, Carlos J.; Correa, Juan Carlos; Marmolejo-Ramos, Fernando (Frontiers in Psychology, 2019)
Elicitation methods aim to build participants’ distributions about a parameter of interest. In most elicitation studies this parameter is rarely known in advance and hinders an objective comparison between elicitation methods. In two experiments, participants were first presented with a fixed random sequence of images and numbers and subsequently their subjective distributions of percentages of one of those numbers was elicited. Importantly, the true percentage was set in advance. The first experiment tested whether receiving instructions as to the elicitation method would assist in estimating a true value more accurately than receiving no instructions and whether accuracy was determined by the numerical skills of the participants. The second experiment sought to compare the elicitation method used in the first experiment with a variation of a graphical elicitation method. The results indicate that i) receiving instructions as to the elicitation method does assist in producing estimates closer to a true percentage value, ii) the level of numerical skills does not play a part in the accuracy of the estimation (Experiment 1) and iii) although the average estimates of the betting and graphical method are not significantly different, the betting method leads to more precise estimations than the graphical method (Experiment 2). Both studies featured statistical procedures (functional data analysis and a novel clustering technique) not considered in past research on the elicitation of subjective distributions. The implications of these results are discussed in relation to a recent key study.